(untitled) (Ágora de Heterodoxias, 2025)
The purpose on the review article is to show how the policies to promote scientific research on tourism in Mexico have had an unfavorable impact on tourism academia and scholars, in addition to the production of cutting-edge knowledge of this discipline within the framework of the SDGs. The problem is the persistence of a policy that is detrimental to the advancement of tourism science, the challenges faced, as well as the training of its professionals. The theoretical-methodological approach implemented is critical-reflexive, with mixed research that correlates conceptual arguments with case study results in academic bodies and graduate students from various universities in Mexico. The discussions and findings show the climate of nonconformity that not only raises the current Law of Humanities, Science, Technology and Innovation (LHCTI), but the effects that it entails in terms of the way of research, the priorities and the results that are being achieved. reaching with an obsolete promotion scheme. The main conclusions aim to integrate the academy in decision-making, but also in new conditions for the promotion of scientific research on tourism in Mexico.